IMPLEMENTASI PERATURAN DAERAH NOMOR 7 TAHUN 2020 TENTANG PAJAK DAERAH DI KABUPATEN GORONTALO UTARA - Nela Karim; Idewi Usman; Tengku Fahrur Gafar (Universitas Bina Taruna Gorontalo, 2024)
This research aims to analyze the description of the implementation of regulation number 7 of 2020 concerning regional taxes in Gorontalo North Regency. The research method used is descriptive with a qualitative approach and literature study. Data collection techniques were carried out through observation, interviews and documentation related to this research. Evaluation of entertainment tax revenue in Gorontalo North Regency until the end of 2020 proves that the percentage of achievement is still low. So it is considered not to meet the planning targets of the Gorontalo North Regency Government. Realization and budget are not comparable. because the object and number of points are clear. Achievement of Regional Original Income from this sector can be achieved. So by optimizing entertainment tax collection it is hoped that it can increase Gorontalo North Regency's Original Income. This research was chosen because it aims to present systematic, factual and accurate data about facts in the field. By using this type of research, you can explore facts about the implementation of Gorontalo Regency Regulation Number 7 of 2020 concerning Regional Taxes. The results of the research show that the implementation of Gorontalo North Regency Regional Regulation Number 7 of 2020 concerning Regional Taxes has gone well but has not been optimal. The benchmarks for determining the success of implementing Gorontalo North Regency Regional Regulation Number 7 of 2020 concerning Regional Taxes are through communication, resources, disposition and bureaucratic structure.